Reactive applications with Akka.NET - Brown, Anthony (Manning Publications Co., 2019)
Chapter 8. Composing actor systems -- 8.1. Introducing Akka.NET remoting -- 8.2. Preparing to use remoting -- 8.3. Communicating with remote actors -- 8.4. Elastic scale across machines -- 8.5. Failure handling across machines -- 8.6. Akka. Remote security -- 8.7. Case study: Remoting, network applications, web server, and backend server -- Summary -- Part 3. Real-life usage -- Chapter 9. Testing Akka.NET actors -- 9.1. Introducing Akka. TestKit -- 9.2. Unit testing actors -- 9.3. Integration testing actors -- 9.4. Testing distributed applications with MultiNode TestKit.